The Influence Of Perceived Convenience, Perceived Useful-ness, And Perceived Risk On Interest In Using E-Commerce - Taufik R., Fikha Zahirah; Harris, Lutfi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The rapid development of information and communication technology has transformed how people perform activities, including business transactions. This study aims to analyze the influence of perceived ease of use, perceived usefulness, and perceived risk on the intention to use e-commerce. The theoretical framework is based on the Technology Acceptance Model (TAM) and Perceived Risk Theory. Data were collected through questionnaires distributed to 119 Accounting students at Universitas Brawijaya and analyzed using multiple linear regression with IBM SPSS 29. The findings indicate that perceived ease of use and perceived usefulness significantly affect the intention to use e-commerce, highlighting the importance of simplicity and efficiency in encouraging technology adoption. In contrast, perceived risk does not significantly influence intention, suggesting that risks such as fraud or product mismatches are not major barriers for users. This study validates TAM and provides practical insights for businesses to improve e-commerce platforms, particularly by focusing on ease of use and utility. Future research should explore additional factors like trust and user experience to deepen the understanding of e-commerce adoption.